The Impact of Remittances on Central Bank Balance Sheets and Inflation in Nepal - Maskay, Nephil Matangi; Steinkamp, Sven; Westermann, Frank (NRB Economic Review, 2015)
Starting from a set of stylized central bank balance sheets, we analyze how central bank policies influence the inflationary impact of remittances. We also estimate the impact of remittances on inflation empirically, using a Vectorautoregression (VAR) framework and a quarterly data set from Nepal. We find this impact to be positive, even after controlling for inflation from India. The domestic monetary base, on the other hand, has lost significance as an independent factor for inflation in the latest 10 years of our sample period. This evidence is consistent with the "impossible trinity" hypothesis. In the conclusions we discuss policy options to accommodate large remittances inflows.